Effects of lightweight fly ash aggregate properties on the performance of lightweight concretes - Koçkal, Niyazi Uğur. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Only a very small content of ash is being used for the construction applications. As large quantities of the fly ash remain unutilized in most countries of the world, the manufacture of light-weight fly ash aggregates is an appropriate step to utilize a large quantity of fly ash. Structural lightweight concrete mixtures can be designed to obtain similar mechanical and durability performance as normalweight concrete. The study is divided into two parts. In the first part of the study, the characteristics of different lightweight fly ash aggregates were investigated. Specific gravity, water absorption, porosity, thermal behaviour, crushing strength and microstructural changes of these aggregates were determined. The properties and microstructure of aggregates were modified by different sintering agents and heat treatments. The strength and specific gravity of all aggregates decreased with increasing the binder content (disregarding binder type) at high temperature. Aggregates with low water absorption and high strength can be attributed to the discontinuous porosity, dense structure and small pore size. In the second part of the study, the influence of properties of lightweight aggregate types on the behaviour of concrete mixtures were discussed. The compressive strength, modulus of elasticity, splitting tensile strength tests, water impermeability test, rapid chloride permeability test, accelerated corrosion studies and rapid freeze/thaw cycling test were performed on lightweight and normalweight concretes. The results of this study revealed the possibility of manufacturing high-strength air-entrained lightweight aggregate concretes using sintered and cold-bonded fly ash aggregates. The use of lightweight aggregates instead of normalweight aggregates in concrete production decreased the strength as expected but improved the resistance to permeability and freeze-thaw of the concretes.
Keywords: Fly ash.; Aggregates (Building materials).; Lightweight concrete.